Phytotherapy of nephrotoxicity-induced by cancer drugs: an updated review - Heidari-Soreshjani, Saeid; Yang, Qian (Journal of nephropathology, 2017)
Context: Kidney is one of the vital organs maintaining homeostasis of body and thus dysfunction of kidney affects quality of life and health severely. Anticancer drugs,particularly chemotherapeutic agents, cause high toxicity leading kidney dysfunction and irreparable kidney injury. Therefore, attention has recently been paid to seeking out alternatives such as nature-based drugs that are effective but less toxic. In this regard, this systematic review article is to report and introduce the most important medicinal plants and their derivatives that are used to reduce anticancer drug-induced nephrotoxicity. Evidence Acquisitions: The word nephrotoxicity alongside the words cancer or chemotherapy in combination with some herbal terms such as medicinal plant, plants, herbs, and extracts were administered to search for relevant publications indexed in PubMed. Results: According to this study, 16 medicinal plants, 12 plant-based derivatives, and three traditional plant-based formulations were found to help control and modulate anticancer drug-induced nephrotoxicity indices. Conclusions: Anticancer drugs cause nephrotoxicity through activating pathways of oxidative stress,damage-associated molecular patterns (DAMPs) production, inflammatory processes, and cell apoptosis, while medicinal plants and their derivatives can cause reduction in nephrotoxicity and anticancer drugs side effects via their antioxidant and anti-inflammatory properties.
Gesehen am 10.04.2018